Effects of chewing gum on driving performance as evaluated by the STISIM driving simulator - Yoo, Ingyu (J Phys Ther Sci, 2015)
[Purpose] The purpose of this study was to determine the effects of chewing gum on driving performance in a driving simulator. [Subjects] In total, 26 young licensed drivers participated. [Methods] The driving scenario was typical of an urban environment: a single-carriageway, two-way road consisting of a mix of curved and straight sections, with considerable levels of traffic, pedestrians, and parked cars. Mean distance driven above the speed limit, lane position, mean distance driven across the center line, and mean distance driven off the road were used as estimates of brake, accelerator, and steering control. The results were compared with those of a non-chewing gum control condition. [Results] The driving performance while chewing gum was significantly better: the mean distance driven above the speed limit was 26.61% shorter, and the mean distance driven off the road was 31.99% shorter. Lane position and mean distance driven across the center line did not differ significantly between the two conditions. [Conclusion] Chewing gum appears to enhance driving performance during a sustained attention driving task.